تقییم دور الجامعات المصریة في تنمیة ثقافة ریادة الأعمال لدي الطلاب - إست ا رتیجیة مقترحة للتحسین- - aramidi, bassam amire (Finance and Business Economies Review, 2018)
Studying entrepreneurship has grown in universities around the world, given its economic and social development, the creation of many jobs for young people, and the creation of innovative and entrepreneurial individuals. The aim of this study is to evaluate the role of the Egyptian universities in developing the culture of entrepreneurship among students, as well as obstacles faced. To achieve the objectives of the study, the researcher distributed 1200 electronic and paper survey forms on a random sample of staff in the Egyptian universities. The analysis was based on an analysis of 891 valid forms. The study found that there is a clear lack of the role of universities in developing a culture of entrepreneurship among students in all areas including vision, mission and strategy, leadership and governance, resources and infrastructure, education for leadership, university support, internationalization and external university relations, and evaluation of entrepreneurship. The study concluded with a proposed strategy to improve the role of the Egyptian universities in developing a culture of entrepreneurship among students.